Role Of Aromatherapy On Anxiety, Pain, Sleep Quality, And Hemodynamic Parasmetrs In Burn Patients; A Systematic Review Of Clinical Trials - Hormoz Mahmoudvand (CV. Inara, 2023)
Aromatherapy refers to the use of volatile oils or aromas extracted from plants for therapeutic purposes. The present study was intended to systematically review the effects of aromatherapy with various essential oils in burn patients. This review was according to the 06-PRISMA standards by searching in the English databases such as Google Scholar, PubMed, Scopus, Web of Science, and ScienceDirect to find papers about the effects of aromatherapy with herbal essential oils in burn patients with no time limitation. We used the keywords of “lavender”, “rose”, “essential oil”, “aromatherapy”, “burn”, “anxiety”, “pain”. From 6630 papers, 10 articles up to June 2022, met the inclusion criteria for analysis in the current systematic review. The most studies were carried out on the effect of aromatherapy with rose essential oil (4, 40%), lavender essential oil (3, 30%), lavender along with rose essential oil (2, 20%), and lavender along with chamomile (1, 10%), respectively. The findings of the current systematic review revealed that aromatherapy especially with lavender and rose essential oil can improve the anxiety, pain, sleep quality, and hemodynamic parameters in burn patients. Hence, due to the convenience of using this method and the lack of reports of any complications and also the stability of hemodynamic status of patients in this method, it is recommended to use it for burn patients.